1672a Managing psychosocial working conditions within ireland and the uk. (24th April 2018) - Kerr, R; Buckley, P
Abstract : The psychosocial domains identified by the Management Standards are essentially bipolar in nature as they carry both pathogenic and salutogenic potential. Consider, for example, the psychosocial hazard of social support at work, where a multitude of studies have shown that low levels of support may have a negative impact on an individual's health; yet, conversely, high levels may protect and enhance it. Psychosocial work interventions such as the HSE's Management Standards can move beyond an exclusive focus on risk assessment and reducing the number of employees at the bottom end of the mental health spectrum toward embracing the potential to make a positive contribution to the mental health of the workforce as a whole. This presentation will explore the recent advancements made in managing psychosocial working conditions within Ireland and the UK. We will describe how the Irish Health and Safety Authority and State Claims Agency have recently embraced a 'positive' approach to psychosocial risk management through the Work Positive CI online tool. Work Positive CI assesses workplace stressors, employee psychological wellbeing and critical incident exposure in the workplace and places a focus on developing clear action plans. We will also present some initial research findings lending further support to a balanced approach. In addition, we describe the results of a population intervention by the UK's Health and Safety Executive (HSE) to decrease the psychosocial risks in the UK population using the Management Standards approach 2004–2010 and discuss current policy and future HSE interventions on work related stress, in schools in Liverpool, NHS Trusts in Scotland and correctional facilities in the North West of England 2016–2020.